Streamlining the formation of learning competence in early childhood from the perspective of educational counseling management - STEGARESCU, Lilia (Acta et Commentationes, Sciences of Education, 2023)
The article contains an introductory foray into explaining and defining the concepts of learning, learning competence and school learning. The specifics of learning as a process, as a product and as a function are specified; the difficulties encountered by students and teachers in training the learning competence of primary school students are delimited. The author reproduces a fragment of research on the efficiency of the formation of learning competence in primary school students, describing essentially and explicitly the possibilities of educational counseling from the perspective of capitalizing on the management of educational counseling.